Pengaruh Board Diversity Terhadap Konservatisme Akuntansi (Studi Empiris Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia 2017-2019) - Fitra Dharma; Lia Ulviana; Yunia Amelia (Universitas Widyatama, 2022)
This study aims to examine and obtain empirical evidence of the influence of female Chief Executive Officer (CEO), female Chief Financial Officer (CFO), female Board of Commissioners on accounting conservatism in all companies listed on the IDX in 2017-2019. The sample of this research is all companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2019 period. The sample selection in this study using purposive sampling method, obtained 124 companies and multiplied during the year of the study, so that the total sample in this study was 372. The dependent variables used in this study were accounting conservatism, female CEO, female CFO, and female Board of Commissioners as independent variable. Tests in this study using analysis tools E-Views (Econometric Views) and for data analysis in this study using linear regression analysis. The results of this study indicate that female CEOs, female CFOs, and female Board of Commissioners have no significant effect on accounting conservatism